Contrasting effects of carbon source recalcitrance on soil phosphorus availability and communities of phosphorus solubilizing microorganisms. (15th November 2021) - Huang, Yanlan; Dai, Zhongmin; Lin, Jiahui; Qi, Qian; Luo, Yu; Dahlgren, Randy A.; Xu, Jianming
Abstract: Carbon (C) additions to soil interact through chemical and microbiological processes to cause changes in soil phosphorus (P) availability. However, the response of soil P transformations and relevant microbial communities to C additions having different degrees of recalcitrance remains uncertain. We studied the effects of glucose, hemicellulose and lignin addition on soil P availability, P transformation processes and relevant microbial activity and communities in a P-deficient flooded soil. Lignin significantly increased soil available P concentrations, which was attributed to chemical release of inorganic P and increased alkaline phosphatase activity. Glucose and hemicellulose additions stimulated microbial metabolism of C thereby enhancing microbial demand for P, with increased soil P availability especially in the early incubation period. Glucose or hemicellulose addition changed soil microbial diversity and community composition, leading to enhanced growth and interactions of P solubilizing microorganisms such as Desulfitobacterium, Bacillus and Desulfosporosinus . Our results infer the importance of pH alteration and competitive sorption between PO4 and functional groups of recalcitrant C ( e.g., lignin) with Fe/Al (hydr) oxides in regulating soil P availability. Further, the microbial response to labile C additions led to increased P availability in the P-deficient soil. This study provides important mechanistic information to guide microbially-regulated soil P management in agricultural ecosystems. Highlights: We investigated the effects of three C sources on microbial- and chemical-regulated soil P availability. Lignin increased available P concentration by increasing pH and competitive sorption with P-sorbing minerals. Glucose and hemicellulose increased soil P availability in the early incubation period. Changes in bacterial communities caused by glucose and hemicellulose contributed to increased P availability.